'I Will Go to the Game, While You Stay Home with the Kids': Gender Role Expectations and Sport Fan-Family Conflict. Issue 1 (2nd January 2023) - Grappendorf, Heidi; Simmons, Jason; Hancock, Meg
Abstract: Within the sport management literature, fan-family conflict is defined as the extent of the role of being a sport fan interferes with one's family role demands. This paper is specifically focused on exploring the dynamics and gender role expectations of highly identified sport fans and their family role. To better understand family dynamics and gender role expectations in navigating fan-family conflict, this study used qualitative approach. Interviews were completed with 21 participants, including 11 men and 10 women ranging in age from 25 to over 65. Data were coded and the content of the responses analyzed for themes, which were then coded into category headings. Results suggested a reliance on traditional gender roles that resulted in both time and strain-based conflict.